2015
DOI: 10.5853/jos.2015.17.3.238
|View full text |Cite
|
Sign up to set email alerts
|

Vessel Wall Imaging of the Intracranial and Cervical Carotid Arteries

Abstract: Vessel wall imaging can depict the morphologies of atherosclerotic plaques, arterial walls, and surrounding structures in the intracranial and cervical carotid arteries beyond the simple luminal changes that can be observed with traditional luminal evaluation. Differentiating vulnerable from stable plaques and characterizing atherosclerotic plaques are vital parts of the early diagnosis, prevention, and treatment of stroke and the neurological adverse effects of atherosclerosis. Various techniques for vessel w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
120
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(127 citation statements)
references
References 133 publications
(187 reference statements)
1
120
0
6
Order By: Relevance
“…The stroke mechanisms were classified by modifying the TOAST (Trial of Org 10172 in acute stroke treatment) classification: large artery atherosclerosis, small vessel occlusion, cardioembolism and dissections [5, 6]. Large artery atherosclerosis was divided according to the site of significant (>50%) stenosis at the relevant distal or proximal VA. Dissection was diagnosed based on the clinical and imaging findings of MR angiography, CT angiography, high-resolution MR or digital subtraction angiographies [7, 8]. The common LMI manifestations – vertigo/dizziness, nystagmus, headache, facial palsy, dysarthria, dysphagia, sensory changes, ataxia, hoarseness and hiccup were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…The stroke mechanisms were classified by modifying the TOAST (Trial of Org 10172 in acute stroke treatment) classification: large artery atherosclerosis, small vessel occlusion, cardioembolism and dissections [5, 6]. Large artery atherosclerosis was divided according to the site of significant (>50%) stenosis at the relevant distal or proximal VA. Dissection was diagnosed based on the clinical and imaging findings of MR angiography, CT angiography, high-resolution MR or digital subtraction angiographies [7, 8]. The common LMI manifestations – vertigo/dizziness, nystagmus, headache, facial palsy, dysarthria, dysphagia, sensory changes, ataxia, hoarseness and hiccup were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…3 Vessel wall enhancement can also be seen in such other arterial diseases as atherosclerosis, moyamoya disease and vasculitis. 4 Nevertheless, taking account of the change in geometry and the persistent vessel wall enhancement together, we concluded that the dissection had progressed despite conservative treatment.…”
mentioning
confidence: 84%
“…Nevertheless, recent studies have indicated that digital subtraction angiography (DSA) [6,7] and high-resolution magnetic resonance imaging (HR-MRI) are useful for evaluating and understanding arterial dissection [8].…”
Section: Using the Region Of Interest Frommentioning
confidence: 99%
“…We identified atherosclerosis based on previously reported important components, including atherosclerotic plaques, lipid cores, fibrous components, intraplaque hemorrhage, and calcium [8,12].…”
Section: Imaging Protocolmentioning
confidence: 99%